ANALISIS KINERJA UNDER FREQUENCY RELAY PADA SUBSISTEM KELISTRIKAN BALI SAAT KONDISI ISLAND OPERATION - Fajar Rizky Kurniawan; I G. Dyana Arjana; Rukmi Sari Hartati (Jurnal SPEKTRUM, 2020)
An electric power system will get overload disturbance if a plant that was previouslyable to supply power to a system that is outage, causes other plants that are still operating tohave the entire load of the system. This study aims to see the performance of under frequencyrelay (UFR) that has been installed in the Bali system in overcoming overload disturbances,namely in the form of generator outages according to the scenario that has been made. Themethod used is to model the load shedding scheme using UFR in software and run according tothe scenario. The scenario referred to is a disturbance that causes one or more generators toexperience blackouts due to disturbances. The results of the analysis show that under thefrequency relay (UFR) installed in the Bali system it cannot return the system frequency to itsnormal state, namely the system has a shortage of generating power with a steady statefrequency below 49.8 Hz in the 3rd, 4th fault scenarios. , and the 5th while the system hasexcess power generation with a stable state frequency above 50.2 Hz at the 9th and 10thdisturbances.